Pop A Little Pancake! - Kubler, Annie, 1960-; Dellow, Sarah (Auburn, ME : Child's Play, 2021)
An illustrated board book with words and music to a children's song.
new kids book 2025 summer.
Keywords: Human body -- Songs and music -- Juvenile literature; Songs -- Juvenile literature; Singing games -- Juvenile literature; Board books; Children's music